2019
DOI: 10.3390/nu11092035
|View full text |Cite
|
Sign up to set email alerts
|

Improved Eating Behaviour and Nutrient Intake in Noncompliant Patients with Phenylketonuria after Reintroducing a Protein Substitute: Observations from a Multicentre Study

Abstract: Noncompliance is widespread in adults with PKU and is associated with adverse metabolic, nutritional and cognitive abnormalities. Returning to the PKU diet is important for this at-risk population, yet for many this is challenging to achieve. Strategies that ease the return to the PKU diet, while offering nutritional and cognitive advantages, are needed. Twelve PKU adults (33.7 ± 2.6 years), who had been noncompliant for 4.5 years (range: 1 to 11 years), took 33 g of a low-volume, nutrient-enriched, protein su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 33 publications
(48 reference statements)
0
8
0
Order By: Relevance
“…The ability to conduct a research study is particularly difficult when the patients are predominantly noncompliant PKU and are disengaged from active metabolic follow-up, highlighting the challenges in their inclusion in relatively complicated research procedures. This has done recruitment particularly difficult and the design of a randomized control trial study complex, as recently reported by Green et al [38].…”
Section: Limitationsmentioning
confidence: 99%
“…The ability to conduct a research study is particularly difficult when the patients are predominantly noncompliant PKU and are disengaged from active metabolic follow-up, highlighting the challenges in their inclusion in relatively complicated research procedures. This has done recruitment particularly difficult and the design of a randomized control trial study complex, as recently reported by Green et al [38].…”
Section: Limitationsmentioning
confidence: 99%
“…Compliance is critically related to patient knowledge on his/her condition, and to factors influencing motivation and attitude [ 7 , 32 ]. In this framework, it is crucial to implement a patient tailored approach to improve long-term adherence to diet treatment and prevent the nutritional, metabolic and cognitive abnormalities associated to non-compliance [ 6 , 32 , 35 ]. Accordingly, doctor-patient communication and relationship between patient and healthcare system should be seriously considered as a main factor facilitating adherence and engagement in the management of PKU, particularly during transition and in adults [ 5 , 7 , 10 ].…”
Section: Resultsmentioning
confidence: 99%
“…While simple in theory, research demonstrates the return to strict adherence is extremely difficult [34], with many patients again nonadherent after several months. Based on recent data, new methods are emerging that can be effectively used to re-engage nonadherent PKU patients in their dietary management through a low burden regimen with immediate nutritional and possible mood benefits [35]. A stepwise approach with the overarching aim of achieving full dietary adherence over a set time may therefore be a more appropriate approach to facilitate patients’ return to the PKU diet but should be confirmed with further research.…”
Section: Discussionmentioning
confidence: 99%